OPTIMALISASI KINERJA ORGANISASI MELALUI MANAJEMEN KERJA HYBRID: MENGATASI DIGITAL BURNOUT DAN RETENSI TALENTA BAKAT - Rida Justin Jacobalis (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The post-pandemic workplace transformation has accelerated the adoption of hybrid work systems that integrate remote and on-site arrangements. While hybrid work offers flexibility and operational efficiency, it also introduces structural challenges, including digital burnout, fragmented organizational culture, and talent retention risks. This study develops a conceptual model integrating hybrid work management, digital burnout, trust-based culture, digital leadership, and organizational performance using a systematic literature review (SLR) grounded in the Job Demands–Resources (JD-R) framework. The findings suggest that hybrid work produces dual effects: it enhances job resources such as flexibility and autonomy, while simultaneously intensifying digital job demands. When job demands exceed available resources, digital burnout emerges as a mediating mechanism that negatively affects performance and talent retention. Trust-based culture and digital leadership function as moderating buffers that mitigate these adverse outcomes. Theoretically, this study extends the JD-R framework into the hybrid work context by positioning digital burnout as a systemic consequence rather than an individual weakness. Practically, the findings provide strategic guidance for designing sustainable and governance-oriented hybrid work systems.